PEMANFAATAN ZEOLIT ALAM ENDE UNTUK MENINGKATKAN KADAR HARA PUPUK ORGANIK - Antonny Bani, Gregorio (Universitas Gajah Putih, 2022)
Indonesia is an agrarian country. Therefore, the method of cultivating agricultural crops needs to be continuously improved through various methods. It starts from land management techniques, the use of pesticides, manufacture of superior seeds, to innovations that produce fertilizers in an effort to increase crop productivity. The use of organic fertilizers are very good in increasing nutrient content and plant growth, but organic fertilizers on the market generally have low nutrient content and slow nutrient supply compared to inorganic fertilizers. Therefore, to increase the nutrient content in organic fertilizers, it is necessary to formulate fertilizers with mineral enrichment into organic fertilizers such as those found in mineral zeolites. The Zeolite mineral is broken down. Then, it is ground into a fine powder and is sieved, physically activated through a heating process in an oven at a temperature of 300 - 4000C for 3 hours. Organic fertilizers are sifted and weighed, put into containers with variations in weight, namely 25; 50 and 75 g. Zeolite was mixed with samples of organic fertilizer until it becomes a homogeneous colloid with a weight ratio of 25 g Zeolite: 75 g fertilizer, 50 g Zeolite: 50 g fertilizer and 75 g Zeolite: 25 g fertilizer. The results showed that mixing Zeolite into organic fertilizer was able to increase the levels of macro nutrients in organic fertilizers, except for the levels of N nutrients contained in organic fertilizers. The best composition for a mixture of Zeolite and organic fertilizer in regular fertilization is a mixture of x1 (25 g Zeolite and 75 g organic fertilizer or a ratio of 1: 3), to prepare land as a planting medium is a mixture of x2 (50 g Zeolite and 50 g organic fertilizer or a ratio of 1:1), and if it will be used to repair the damage to the physical and chemical properties of the soil, the mixture is x3 (75 g Zeolite and 25 g organic fertilizer or a ratio of 3: 1).